METHODICAL APPROACHES TO THE STUDY OF THE TRAJECTORY OF THE DEVELOPMENT OF REGIONAL THE SOCIAL NATURE OF ECONOMIC SYSTEMS - N. N. Kiseleva (Современная наука и инновации)
The article presents the author's method of construction of integral indicators that characterize the trajectory of development of regional social nature of economic systems. This methodology enables to identify the vector of regional development and regional variability reproduction proportions in time, and also make a comparative analysis of the development of different regions, to determine the scale of interregional differentiation. Approach to an assessment of structural shifts in branch structure of economy of the region is stated.